NMC: A Fast and Secure ARX Cipher - Noureldien, Noureldien A.; Hassan, Mustafa B. (Transactions on Engineering and Computing Sciences, 2023)
Fastening complex computing tasks and reducing latency have become essential in areas such as cryptography, robotics, natural-language processing, and video streaming. This is because even a few milliseconds can have a significant impact on the operation, performance, and computational cycle consumption of the algorithm. This paper introduces a new ARX cipher design called NMC. NMC is a fast and secure stream cipher and it generates keystream bytes solely from secret key bits and plaintext message length. NMC has high randomness, long keystream period, and one time pad (OTP) keystream production. Experimental testing confirmed the randomness of the keystreams and showed that NMC has marginally better speed performance than RC4 for short messages but is slightly slower for messages of average length and slightly large messages. NMC’s synchronization mode showed that the keystream period is long and NMC achieved OTP keystream production. The results indicate that NMC is a competitive and promising cipher algorithm.